Psychosocial risks and protective factors of suicidal behaviors among youths in Saudi Arabia: A cross-sectional study - Ahmed, Hanem Ahmed AbdElkhalek; Abd El-Maksoud, Mona M; Jeyapaul, Shylaja; Elsayed, Eman Baleegh Meawad; Rani, Vanitha Innocent; Aseeri, Abeer S.; Asiri, Manal Ibrahim (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Youth suicidal behavior is a critical public health concern worldwide. Addressing suicidal behaviors among youth is essential; however, limited research has explored the complex relationships between psychosocial risk and protective factors influencing suicidal behavior in Saudi youth, especially within their unique cultural and religious context. Bridging this gap is vital for developing culturally sensitive prevention strategies. Objective: This study aimed to investigate psychosocial risk and protective factors associated with suicidal behaviors among Saudi youth. Methods: A cross-sectional descriptive study was conducted from May to August 2024 with 400 university students. Data were collected using standardized and validated instruments. Statistical analyses included chi-square tests to explore demographic associations with suicide risk, correlation matrices, a suicide heatmap to visualize factor interrelations, scatterplots, and multiple linear regression to identify significant predictors. Results: Findings showed that 11.8% of youth were classified as at suicidal risk. Suicide risk behavior correlated positively with life stressors (r = 0.60, p <0.01) and interpersonal needs—perceived burdensomeness and thwarted belongingness (r = 0.31, p <0.01)—and negatively with resilience (r = -0.10, p <0.01) and perceived social support (r = -0.22, p <0.01). The regression model significantly predicted suicide risk behavior (F(4, 748) = 61.89, p <0.001), explaining 38.5% of the variance (Adjusted R² = 0.379). Life stressors (β = 0.562, p <0.001) and interpersonal needs (β = 0.115, p = 0.009) were significant positive predictors, while resilience and social support were not significant predictors. Conclusions: Although suicide prevalence among Saudi youth is relatively low, a significant minority remains at risk, particularly those experiencing family problems, low income, and who have no friends. Life stressors and unmet interpersonal needs are major risk factors. These findings emphasize the vital role of nursing practice in suicide prevention through routine screening, counseling, stress management, and fostering social support. Integrating these strategies in academic and community settings can enhance mental health outcomes and reduce suicide risk among Saudi youth.